Memory-free loading paths for a coupled continuous contact problem with friction - Cwiekala, N; Barber, JR; Hills, DA (Elsevier, 2022)
The plane elastic problem of a circular disk shrink fitted into a hole in an elastically similar plane, with a frictional interface, is studied subject to the application of a radial force and torque both of which vary with time. This is done by the use of edge dislocation distributions to represent slip. The evolution of extent and position of a slip zone as well as the magnitude of slip displacements is studied. Conditions for continuous slip, leading a history or load path independent solution are derived. The results derived prepare for the study of the shakedown behaviour of a continuous coupled contact.